PERBEDAAN PELATIHAN JALAN DENGAN STATIC BICYCLE TERHADAP VO2 MAX, INSPIRASI MAKSIMAL, DAN HEART RATE PADA LANSIA - Prabowo, Eko; bagiada, Agus; Imron, M Ali (Sport and Fitness Journal; Volume 4, No. 2, 2016)
Endurance cardiorespiratory is an ability of someone to exercises longer without anyfatigue. Endurance cardiorespiratory was influenced by the heart endurance, muscleendurance and respiratory function. In the elderly due to an oxidative stress, the conditionwhere free radicals is much more than anti oxidant in our body. It will produce oxidative damage of cell/tissue leads to aging and death.Thepurpose of the study is to determinedifferences in the increased in VO2 max, decreased heart rate and increased maximalinspiration between the moderate intesity walking and moderate intensity stationerybicycle.This study is clinical experimental studyusing methods pre test and post test groupdesign. Sixteen subjects of elderly people devided in to two groups. The first group of 8subjects gived the moderate intesity walking for 30 minutes exercise, 3 times a week. Thesecond group of 8 subjects givedthe moderate intesity stationery bicycle for 30 minutesexercise, 3 times a week. total peroid of exercise was 8 weeks. VO2 max measure a using the6 walking minute test, resting heart rate test using a stopwatch and maximal inspiration usingincentive spirometry manual. Results of this study: the mean value Vo2 max afterintervention ofgroup I was 20.82 ml/kg/min and group II was 20.62 ml/kg/minthe differentmean between two groups was 0.2 ml / kg / min and showed no significant difference (p =0.43). The mean value resting heart rate after intervetion of group I was 66 beats/min andgroup II was 66.62 beats/min the different between the two groups was 0.62 beats / minuteand showed no significant difference (p = 0.702), The mean value maximum inspiration afterintervention of group I was 1937.5 ml and group II was 1912,5 ml the different meanbetween two groups was25 ml and showed no significant difference (p = 0.480). It wasconcluded thatthere were nodifferences between moderate intesity walking and moderateintensity stationery bicycle on the increase VO2 max, decrease heart rate, and increasemaximum inspiration in the elderly.
Keywords: VO2 max, heart rate, maximum inspiration, moderate intesity walking, moderate intensity stationery bicycle